Functionalized DNA hydrogel and its application in preparation of ophthalmic medical devices

CN122879252APending Publication Date: 2026-10-09TIANJIN EYE HOSPITAL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611033275.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-13
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0003]但OK镜作为硬性接触镜,长期夜间佩戴过程中存在三大突出安全痛点,严重影响其临床安全性和佩戴舒适度,甚至限制其推广应用:

Benefits of technology

本发明所述的功能化DNA水凝胶延续了sDNA体系“液态前驱体-原位成胶”的核心优势,各组分在混合前保持流动状态,混合后在生理条件下可控形成稳定的三维网络结构,实现由液态向凝胶态的转变。这种可注射、原位成胶的特性不仅提升了材料的操作便利性,也为局部微创给药提供了重要技术基础。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122879252A_ABST
    Figure CN122879252A_ABST
Patent Text Reader

Abstract

The application provides a functionalized DNA hydrogel and application thereof in preparation of ophthalmic medical devices, wherein the DNA hydrogel comprises EA modules and EB modules; the EA module comprises six DNA chains, namely E1, E2, E3, E4, E5 and E6. The functionalized DNA hydrogel continues the core advantage of the sDNA system, that is, a liquid precursor forms a gel in situ, each component keeps a flowing state before mixing, and a stable three-dimensional network structure can be formed under physiological conditions after mixing, so that the transformation from a liquid state to a gel state is realized. The injectable and in-situ gelation characteristics not only improve the operation convenience of the material, but also provide an important technical basis for local minimally invasive drug delivery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of medical devices, and in particular relates to a functionalized DNA hydrogel and its application in the preparation of ophthalmic medical devices. Background Technology

[0002] Orthokeratology (OK) lenses are currently recognized as a core medical device for myopia control in adolescents. They are high-oxygen-permeable rigid contact lenses with a reverse geometry design. When worn overnight for 8-10 hours, they gently reshape the central cornea by utilizing eyelid pressure and tear fluid dynamics, temporarily reducing myopia and achieving clear uncorrected vision during the day. At the same time, OK lenses can cause myopic defocus in the peripheral retina, effectively slowing down axial elongation and reducing the risk of adolescents developing high myopia. They have been widely used in clinical myopia control.

[0003] However, as a rigid contact lens, orthokeratology (Ortho-k) lenses present three major safety concerns during long-term nighttime wear, severely impacting their clinical safety and wearing comfort, and even limiting their widespread application: 1. Risk of mechanical abrasion of the cornea: Orthokeratology (Ortho-k) lenses are relatively hard. During sleep at night, there will be continuous mechanical friction between the lens and the corneal epithelium. Especially when the wearing position is off, the lens is not well-fitting, or the sleeping posture changes, it is easy to cause micro-abrasions on the corneal surface. According to clinical data, about 30% of Ortho-k lens wearers will experience varying degrees of micro-damage to the corneal epithelium. Long-term repeated abrasions will damage the corneal barrier function, increase the risk of subsequent infection, and in severe cases, can lead to corneal epithelial erosion and ulceration.

[0004] 2. Risk of eye infection: After corneal abrasion, the corneal epithelial barrier is damaged, making it easier for bacteria, fungi, and other microorganisms in tears to invade corneal tissue and cause eye infections such as keratitis and conjunctivitis. Clinical studies have shown that the incidence of eye infections related to orthokeratology (Ortho-k) lens wear is about 0.1-0.5%. Although the incidence is low, if it occurs and is not treated in time, it may lead to corneal scarring, decreased vision, or even blindness. In addition, inadequate cleaning and improper care of Ortho-k lenses can also increase the risk of infection.

[0005] 3. Worsening of dry eye syndrome: When wearing orthokeratology (Ortho-k) lenses, the lens covers the corneal surface, disrupting the integrity and stability of the tear film and accelerating tear evaporation. At the same time, the mechanical stimulation of the lens inhibits the secretion of mucin by conjunctival goblet cells, leading to a shortened tear film breakup time and causing dry eye symptoms such as dryness, foreign body sensation, and burning sensation. According to surveys, about 50% of Ortho-k lens wearers experience varying degrees of dry eye. Long-term dry eye not only reduces wearing comfort but also further aggravates corneal damage, forming a vicious cycle of "dry eye-corneal damage-infection".

[0006] Currently, the existing solutions for corneal protection issues related to orthokeratology (Ortho-k) lens wear mainly include the following categories, but all of them have significant drawbacks: (1) Artificial tears: As the most commonly used auxiliary means, it is mainly used to relieve dry eye symptoms. However, the retention time of artificial tears on the ocular surface is extremely short (usually <10 minutes), the water-locking and moisturizing effect is poor, it cannot buffer the mechanical friction between the lens and the cornea, and it does not have anti-inflammatory, antibacterial and corneal repair functions. It can only temporarily relieve discomfort and cannot solve the problem from the root.

[0007] (2) Antibacterial eye drops: used to prevent eye infections, but long-term use can easily induce bacterial resistance. They can only target infection problems and cannot solve corneal abrasion and dry eye. In addition, some antibacterial eye drops are irritating to the eyes and are not suitable for people who wear them for a long time.

[0008] (3) Common polymer gels (such as hyaluronic acid gel and chitosan gel): Although they can prolong the time of ocular surface retention and relieve dry eyes, they are not biocompatible. Some gels may cause foreign body sensation and allergic reactions in the eyes. They also lack mechanical buffering capacity, cannot effectively prevent corneal abrasion, and do not have active corneal repair and anti-inflammatory and antibacterial functions, and have poor compatibility.

[0009] (4) Corneal repair drugs: such as recombinant human epidermal growth factor eye drops, which can promote corneal epithelial repair, but the retention time is short, requiring frequent administration, which is inconvenient to use, and cannot simultaneously achieve moisturizing, anti-abrasion and antibacterial functions, thus limiting their clinical application.

[0010] DNA hydrogels are three-dimensional porous biomaterials that are self-assembled based on the complementary base pairing principle of DNA molecules and through programmed design of DNA sequences. They have excellent biocompatibility, complete biodegradability, programmable structure, high water retention and good bioactivity, and have received widespread attention in the biomedical field in recent years, especially in tissue engineering and eye repair.

[0011] Existing research confirms that hydrogels constructed with X-type DNA as a backbone can form a stable covering layer on the ocular surface, prolonging retention time. Their three-dimensional porous structure possesses excellent elasticity and water-locking capacity, maintaining tear film stability and alleviating dry eye. Furthermore, these hydrogels are non-cytotoxic, promoting corneal epithelial cell migration and proliferation, accelerating corneal damage repair, and reducing ocular inflammation. However, currently, there are no technical solutions for directly applying DNA hydrogels to orthokeratology (OK) lenses to specifically address corneal abrasion, infection, and dry eye issues associated with OK lens wear, nor are there any DNA hydrogel products suitable for OK lens wear scenarios that offer multiple protective functions. Summary of the Invention

[0012] In view of this, the present invention aims to overcome the deficiencies in the prior art and proposes a functionalized DNA hydrogel and its application in the preparation of ophthalmic medical devices.

[0013] To achieve the above objectives, the technical solution of the present invention is implemented as follows: This invention provides a functionalized DNA hydrogel, which includes an EA module and an EB module; The EA module comprises six DNA strands, namely E1, E2, E3, E4, E5, and E6. The nucleotide sequence of the E1 DNA strand is shown in SEQ ID NO.1, the nucleotide sequence of the E2 DNA strand is shown in SEQ ID NO.2, the nucleotide sequence of the E3 DNA strand is shown in SEQ ID NO.3, the nucleotide sequence of the E4 DNA strand is shown in SEQ ID NO.4, the nucleotide sequence of the E5 DNA strand is shown in SEQ ID NO.5, and the nucleotide sequence of the E6 DNA strand is shown in SEQ ID NO.6.

[0014] Furthermore, the EB module includes two DNA strands, E7 and E8, with the nucleotide sequence of the E7 DNA strand shown in SEQ ID NO.7 and the nucleotide sequence of the E8 DNA strand shown in SEQ ID NO.8.

[0015] The functionalized DNA hydrogel mainly consists of two functional modules: the EA module and the EB module. The EA module is formed by the assembly of six single-stranded DNA molecules through programmed base pairing; the EB module consists of two single-stranded DNA molecules and is used for subsequent structural ligation and network construction.

[0016] Structurally, the hydrogel consists of two parts: an X-shaped backbone unit and a linker unit. The X-shaped backbone unit is formed by the self-assembly of two 50bp and two 55bp single-stranded nucleic acids through specific base complementary pairing to form a stable, loose, and flexible core (E1, E2, E3, and E4). This structure retains designed sticky ends at the ends, providing binding sites for further network crosslinking.

[0017] The linker unit consists of two complementary linker-DNA sequences. The linker sequences hybridize with complementary regions at the ends of the X-shaped backbone, achieving bridging and spatial extension between backbone units through specific base pairing, thereby driving the orderly connection between multiple units and forming a three-dimensional network structure (E5, E6, E7, and E8).

[0018] To implement a modular assembly strategy, E1-E6 are pre-mixed and constructed as EA modules, while E7 and E8 are combined into EB modules. This modular assembly method achieves higher structural programmability and assembly controllability through functional unit decomposition, which helps to improve system repeatability and structural stability.

[0019] This invention also provides a method for preparing functionalized DNA hydrogels, comprising the following steps: (1) Mix E1 DNA chain, E2 DNA chain, E3 DNA chain, E4 DNA chain, E5 DNA chain and E6 DNA chain, add auxiliary assembly agent to it, and after mixing, obtain a reaction system. Perform thermal annealing on the reaction system to obtain EA module. (2) Mix the E7 DNA strand and the E8 DNA strand, add an assembly aid, and mix to obtain a reaction system. Perform thermal annealing on the reaction system to obtain the EB module. (3) Mix the EA module and the EB module evenly to obtain the final product.

[0020] Furthermore, in step (1), the molar ratio of E1 DNA chain, E2 DNA chain, E3 DNA chain, E4 DNA chain, E5 DNA chain, E6 DNA chain, E7 DNA chain and E8 DNA chain is 1:1:1:1:1:1:1:1.

[0021] Furthermore, the auxiliary assembly agent in step (1) is magnesium sulfate, and the final concentration of magnesium ions in the reaction system in step (1) is approximately 7.5 mM; the working concentration of each DNA strand in the reaction system in step (1) is 800 μM. The auxiliary assembly agent in step (2) is magnesium sulfate, and the final concentration of magnesium ions in the reaction system in step (2) is about 7.5 mM; the working concentration of each DNA strand in the reaction system in step (2) is 800 μM.

[0022] Furthermore, the thermal annealing process in step (1) specifically involves: first holding at 95℃ for 5 minutes, then cooling from 93℃ to 37℃ at a gradient cooling rate of 1℃ / min; the thermal annealing process in step (2) specifically involves: first holding at 95℃ for 5 minutes, then cooling from 93℃ to 37℃ at a gradient cooling rate of 1℃ / min. Thermal annealing achieves ordered hybridization assembly, controls the hybridization kinetics process, and improves the uniformity and stability of the structural assembly.

[0023] This invention also provides the application of functionalized DNA hydrogels in the preparation of ophthalmic medical devices.

[0024] Furthermore, the functionalized DNA hydrogel is used in the preparation of orthodontic devices.

[0025] Furthermore, the functionalized DNA hydrogel is used in the preparation of corneal contact lenses.

[0026] Furthermore, the functionalized DNA hydrogel is used in the preparation of orthokeratology lenses.

[0027] Compared with the prior art, the present invention has the following advantages: The functionalized DNA hydrogel described in this invention continues the core advantage of the sDNA system: "liquid precursor-in-situ gelation." Each component remains in a fluid state before mixing, and after mixing, it can controllably form a stable three-dimensional network structure under physiological conditions, achieving a transformation from a liquid to a gel state. This injectable, in-situ gelation characteristic not only improves the material's handling convenience but also provides an important technical basis for local minimally invasive drug delivery.

[0028] The functionalized DNA hydrogel described in this invention features a simpler structural design, with its backbone components inherently possessing gel-forming capabilities, enabling the formation of a stable network structure. This "backbone as function" design philosophy reduces system complexity while improving structural controllability and reproducibility. The gel-forming process is gentle and controllable, which is beneficial for the encapsulation of bioactive molecules and the safety of in vivo applications.

[0029] The functionalized DNA hydrogel described in this invention overcomes the limitations of traditional DNA hydrogels, which are merely used as carriers or structural scaffolds. It is used as a therapeutic material with intrinsic biological activity, and its interventional role in dry eye syndrome was systematically explored. In vitro and in vivo experiments verified that the hydrogel can form a stable retention on the ocular surface. Its H&E and PAS results demonstrate that the hydrogel can synergistically regulate the ocular surface microenvironment, exerting a dual function of anti-inflammation and tissue repair.

[0030] The functionalized DNA hydrogel described in this invention, while inheriting the advantages of controllable gelation and injectability of the sDNA system, achieves structural simplification and functional enhancement through optimization of the backbone components, and shows good application prospects in the treatment of dry eye syndrome, providing a new approach for the transformation of DNA functional materials in local ophthalmic treatment. Attached Figure Description

[0031] Figure 1 Synthesis of DNA hydrogel according to the embodiments of the present invention: Figure A shows the transition between the liquid and gel states of the hydrogel, and Figure B shows the agarose gel electrophoresis analysis of ssDNA and hydrogel. Figure 2 Scanning electron microscopy imaging of the DNA hydrogel described in the embodiments of the present invention; Figure 3The effect of different concentrations of DNA hydrogel on the viability of HCECs described in this embodiment of the invention: The cell viability of HCECs after treatment with 5, 10, and 20 mM hydrogels was detected by CCK-8 assay. Figure A shows the result after 24 h, Figure B shows the result after 48 h, and Figure C shows the result after 72 h. Figure 4 The effect of the DNA hydrogel described in this embodiment of the invention on the migration ability of HCECs: Figure A shows the cell scratch healing under an optical microscope; Figures B and D show the statistical analysis of cell migration rate at 24h, 48h, and 72h, respectively. Figure 5 The effect of the DNA hydrogel described in this embodiment of the invention on the cell viability of HCECs (live / dead staining): HCECs were co-cultured with 10 mM hydrogel for 24 h and then subjected to Calcein-AM / PI double staining. The results showed that green fluorescence (live cells) was the main feature in the field of view, while red fluorescence (dead cells) was less, indicating that the hydrogel has good cell compatibility. Figure 6 The retention capacity of DNA hydrogels of different concentrations in the cornea as described in the embodiments of the present invention; Figure 7 This is an in vivo safety assessment of the DNA hydrogel eye drop formulation described in this embodiment of the invention in the mouse eye after continuous administration for 2 weeks. Figure 8 The OCT method described in this embodiment of the invention is used to evaluate the effect of DNA hydrogel eye drops on the corneal structure of mice after continuous administration for 2 weeks. Figure 9 Evaluation of the dry eye model described in this embodiment of the invention: Figures AC show corneal fluorescein staining and Schirmer test, and Figure D shows body weight change; Figure 10 The effect of the DNA hydrogel described in this embodiment of the invention on ocular surface repair in a dry eye model mouse: Figure A shows the results of sodium fluorescein corneal staining and statistical analysis of corneal healing rate; Figure B shows the changes in tear secretion in mice detected by the phenol red cotton thread test. Figure 11 The effects of different treatment regimens described in this embodiment of the invention on the ocular surface tissue structure of dry eye model mice are shown in Figure A, which shows the changes in corneal tissue structure observed by H&E staining (scale bar: 50 μm) and Figure B, which shows the distribution of conjunctival goblet cells observed by PAS staining (scale bar: 100 μm). Detailed Implementation

[0032] Unless otherwise defined, the technical terms used in the following embodiments have the same meanings as commonly understood by those skilled in the art. Unless otherwise specified, the experimental reagents used in the following embodiments are conventional biochemical reagents; and the experimental methods described are conventional methods.

[0033] The present invention will be described in detail below with reference to the embodiments.

[0034] Example 1: Synthesis of DNA Hydrogel This invention designs eight different DNA oligonucleotide sequences for constructing DNA hydrogels, which form hydrogels through self-assembly. All DNA oligonucleotide chains are biosynthesized, and DNA samples are dissolved in deionized water.

[0035] In the assembly system, the eight DNA oligonucleotide chains (E1-E8) required for the synthesis of the hydrogel were mixed in an equimolar ratio (E1:E2:E3:E4:E5:E6:E7:E8=1:1:1:1:1:1:1:1) to construct a reaction system with a final XDNA monomer concentration of 100 μM, wherein Mg 2+ The final concentration was 7.5 mM to maintain the stability of the DNA double-stranded structure and promote structural self-assembly.

[0036] The mixed system was subjected to programmed thermal annealing to achieve ordered hybridization assembly: first, it was kept at 95℃ for 5 min to completely denature the single-stranded DNA, and then the temperature was gradually reduced from 93℃ to 37℃ in a gradient cooling manner of 1℃ / min to control the hybridization kinetics process and improve the uniformity and stability of the structural assembly.

[0037] The specific steps are as follows: (1) Take 10 μL of E1 DNA strand, 10 μL of E2 DNA strand, 10 μL of E3 DNA strand, 10 μL of E4 DNA strand, 10 μL of E5 DNA strand, and 10 μL of E6 DNA strand respectively, and mix them. The working concentration of the above DNA strands in the mixture is 800 μM. Add 100 mM of MgSO4 to the mixture, and after mixing, obtain the reaction system. 2+ The final concentration was approximately 7.5 mM. The reaction system was subjected to thermal annealing, held at 95°C for 5 min to completely denature the single-stranded DNA, and then gradually cooled from 93°C to 37°C at a gradient cooling rate of 1°C / min to obtain the EA module. (2) Take 10 μL of E7 DNA strand and 10 μL of E8 DNA strand respectively and mix them. The working concentration of the DNA strands in the mixture is 800 μM. Add 100 mM MgSO4 to the mixture and mix to obtain the reaction system. 2+ The final concentration was approximately 7.5 mM. The reaction system was subjected to thermal annealing at 95°C for 5 min to completely denature the single-stranded DNA. Subsequently, the temperature was gradually reduced from 93°C to 37°C at a gradient cooling rate of 1°C / min to obtain the EB module. (3) Mix the EA module and the EB module evenly to obtain the final product.

[0038] Example 2: Validation of DNA Hydrogel Synthesis To verify the successful assembly of the hydrogel monomer structure and its molecular weight changes, agarose gel electrophoresis was used for analysis. A 3% (w / v) agarose gel was used as the separation medium, and the electrophoresis buffer was 1×TAE buffer. Specifically, 2.4 g of agarose powder was added to 80 mL of 1×TAE, and the mixture was heated until the agarose was fully dissolved. After the solution cooled to approximately 60 °C, 1% of the nucleic acid dye GelRed was added. After the gel solidified, 9 μL of DNA sample was mixed with 1 μL of 10×Loading Buffer, and 5 μL of the mixture was loaded onto the gel. The electrophoresis buffer was 1×TAE, and the experiment was conducted at 8 V / cm for 120 min. Electrophoretic band images were observed and acquired using a gel imaging system. Samples were mixed with an appropriate amount of loading buffer and loaded into the gel wells, and electrophoresis was performed at a constant electric field strength of 8 V / cm for 120 min.

[0039] like Figure 1 As shown in Figure A, both components EA and EB are homogeneous and transparent liquids at room temperature. When mixed at the designed ratio (1:1) and gently blown 3-5 times, the system rapidly changes from a flowing liquid to a viscous state, exhibiting significant viscoelastic characteristics, indicating effective cross-linking and the formation of a three-dimensional network structure. Molecular-level verification was performed using 3% agarose gel electrophoresis. The results showed that the migration rate of the XDNA structural unit was lower than that of the single-stranded raw material, and the band position was consistent with the theoretical molecular weight, proving the successful assembly of the cross-linked structure. Further electrophoretic analysis of the fully assembled hydrogel revealed a distinct retention band at the sample well, accompanied by a certain degree of tailing. Figure 1 As shown in Figure B, the system exhibits a high molecular weight cross-linked network and molecular weight distribution characteristics. These results collectively confirm the successful construction of the three-dimensional supramolecular network structure of the hydrogel.

[0040] Example 3 Characterization of DNA hydrogel microstructure To observe the microstructure and internal network structure of the DNA hydrogel, scanning electron microscopy (SEM) was used for characterization. During preparation, the formed hydrogel samples were pre-frozen and then freeze-dried to remove moisture and maintain the integrity of their three-dimensional structure. The dried samples were then fixed onto a conductive sample stage and subjected to metal sputtering to enhance conductivity.

[0041] Subsequently, under suitable conditions of accelerating voltage of 15.0 kV, observations were conducted to obtain microstructure images at different magnifications. The pore structure, network connectivity, and spatial distribution characteristics of the hydrogel were analyzed using SEM images to evaluate the formation and structural uniformity of its three-dimensional porous structure.

[0042] like Figure 2 As shown, at a monomer concentration of 100 μM, a uniform and continuous three-dimensional porous network structure forms within the hydrogel, with regular pore distribution and a complete structure, indicating that the system can achieve efficient self-assembly and construct a stable spatial cross-linked network at room temperature. This three-dimensional porous structure helps form a stable capping layer on the ocular surface, improving the hydrogel's retention capacity on the corneal surface. Simultaneously, the interconnected pore structure enhances water storage and sustained release capabilities, improving the local moist microenvironment, thereby contributing to maintaining tear film stability and promoting corneal epithelial repair. Furthermore, the dense and uniform network structure provides a structural basis for subsequent loading of bioactive molecules or cells. These results support the potential application of hydrogels in the treatment of dry eye at the microstructural level.

[0043] Example 4: Effect of DNA hydrogel on HCEC cell viability This invention uses human corneal epithelial cells (HCECs). Cell culture is performed using DMEM / F-12 (1:1) complete medium supplemented with 10% fetal bovine serum (FBS) and 1% penicillin-streptomycin antibiotics to prevent microbial contamination.

[0044] Cells were cultured at 37 ℃, 5% CO2, and saturated humidity, with the culture medium changed regularly. Cells were passaged when they reached approximately 80-90% confluence. All in vitro experiments used cells from passages 3-6 to ensure stable cell biological characteristics and minimize the impact of passage differences on experimental results.

[0045] Human corneal epithelial cells (HCECs) were sized at 2.5 × 10⁻⁶. 3 Cells were seeded at a density of 1 / well in 96-well plates and cultured at 37°C and 5% CO2 for 24 h to ensure cell adhesion. Subsequently, different concentrations of pre-prepared hydrogels (0, 5, 10, 20 mM) were added to each group, and the cells were cultured for another 24, 48, and 72 h.

[0046] At each detection time point, CCK-8 working solution (prepared by mixing CCK-8 reagent and complete culture medium at a volume ratio of 1:10) was added to each well, and the mixture was incubated at 37°C for 2 hours. The absorbance (OD) was then measured at 450 nm using a microplate reader. 450 This reflects the level of cell activity. Each experiment was independently repeated three times.

[0047] like Figure 3As shown, after 24 h and 48 h of treatment, there was no statistically significant difference in cell viability between the hydrogel groups at different concentrations and the PBS control group (P>0.05), indicating that the material did not exhibit significant cytotoxicity under short-term exposure conditions. At 72 h, the cell viability of the hydrogel-treated groups decreased compared to the control group, showing a concentration-dependent trend. At 5 mM and 10 mM, cell viability remained above 80%, indicating good cell compatibility of the material in the low to moderate concentration range. In contrast, cell viability further decreased in the 20 mM group, suggesting that higher concentrations may have a certain inhibitory effect on cell proliferation. These results indicate that the hydrogel has good biocompatibility with HCECs within a suitable concentration range.

[0048] Example 5: In vitro evaluation of the ability of DNA hydrogel to promote the migration of HCECs HCECs were 5×10 4 Cells were seeded at a density of approximately 90% confluence in 6-well plates. A uniform artificial damage model was created by vertically scratching the cell monolayer using a sterile 200 μL pipette tip. Cells were then washed twice with PBS to remove detached cells. Different concentrations of hydrogel (0, 5, 10, 20 mM) were added for co-culturing, and images of the same scratched area were recorded at 0, 24, 48, and 72 h. The scratch area was measured using ImageJ software, and cell migration was calculated using the following formula: Cell migration rate = (initial scratch area - final scratch area) / initial scratch area × 100% like Figure 4 As shown, at 24, 48, and 72 h, the cell migration rate of each treatment group gradually increased with time, indicating that cells continued to migrate towards the scratch area. Compared with the PBS control group, the cell migration rate of the 10 mM and 20 mM hydrogel groups was significantly increased at all time points (P<0.05), showing a significant migration-promoting effect. Among them, the medium and high concentration groups showed a more significant promoting effect at 48 h and 72 h, indicating that the hydrogel can enhance the migration ability of HCECs within a certain concentration range.

[0049] The above results suggest that hydrogels can promote corneal epithelial cell migration in vitro, providing data support for their potential application in ocular surface repair and dry eye treatment.

[0050] Example 6 Cell live / dead staining analysis HCECs were 5×10 3Cells were seeded in confocal microplates, and 100 μL of complete culture medium was added to each well for 24 h. Then, 10 μL of hydrogel was added, and incubation continued for another 24 h. After treatment, the cells were gently washed three times with PBS, and Calcein-AM / PI double staining working solution was added. The cells were incubated at 37 ℃ in the dark for 30 min. Fluorescence images were acquired using laser confocal microscopy, where green fluorescence represents surviving cells and red fluorescence represents dead cells, to assess the effect of the hydrogel on cell viability.

[0051] like Figure 5 As shown, 10 mM was selected as the suitable hydrogel concentration for subsequent experiments, and further live / dead cell fluorescence staining analysis was performed. Under this concentration condition, after co-culturing the hydrogel with HCECs for 24 h, fluorescence imaging results showed that Calcein-AM labeled green fluorescence signal dominated the field of view, while PI labeled red fluorescence signal was less, indicating high cell viability and no obvious cytotoxicity. At the same time, the cells were morphologically intact and well adhered, and no obvious apoptosis or necrosis characteristics were observed.

[0052] Example 7: In vivo evaluation of DNA hydrogel prolonging ocular surface retention time All animal experimental protocols were approved by the ethics committee and complied with the relevant guidelines of the Society for Vision and Ophthalmology Research (SIVAR) regarding animal experiments. Six- to eight-week-old female C57BL / 6 mice (weighing 20-25 g) were selected. Animals were housed in a 12-hour light / dark cycle environment at a temperature of 23-25 ​​°C and humidity of 30±3%. The lyophilized hydrogel was dissolved in a solution containing 0.1% sodium fluorescein to assess its ocular surface retention time. Nine mice were randomly divided into three groups (blank control group, and groups with different concentrations of hydrogel (10, 25, 50, and 100 mM)). After 5 μL of eye drops were instilled onto the corneal surface, the distribution of fluorescence on the ocular surface was observed and recorded using a slit-lamp microscope at 0, 5, 10, 15, 30, 60, 120, and 150 min to assess the material's retention capacity.

[0053] like Figure 6 As shown, after simply adding sodium fluorescein solution, the green fluorescence signal on the corneal surface began to weaken significantly within 5 minutes and almost disappeared by 90 minutes, with only a small amount of residual fluorescence visible in the conjunctival sac, indicating that the retention time of free sodium fluorescein on the ocular surface was short. In contrast, the hydrogel loaded with sodium fluorescein significantly prolonged the duration of the fluorescence signal on the cornea. Hydrogels of different concentrations all showed enhanced retention effects, with the 50 mM and 100 mM groups showing more significant prolongation effects, and strong green fluorescence signals could still be observed on the corneal surface after 150 minutes.

[0054] The above results indicate that hydrogels can effectively increase the retention time of drugs on the ocular surface and exhibit good sustained-release potential, suggesting that they have application prospects as a local ocular drug delivery carrier.

[0055] Example 8: In vivo safety evaluation of hydrogels Six mice were randomly divided into two groups, receiving either 5 μL of hydrogel or PBS eye drops twice daily for 14 days. Body weight and intraocular pressure were recorded on days 0, 3, 5, 7, and 14 after administration. Corneal transparency, neovascularization, and fluorescein staining were examined using a slit lamp. Corneal thickness and structural changes were monitored using optical coherence tomography (OCT) on days 0, 7, and 14. Mice were anesthetized with 1.25% ready-to-use tribromoethanol via intraperitoneal injection before OCT imaging to systematically evaluate the in vivo safety of the hydrogel.

[0056] like Figure 7 As shown, compared with the PBS control group, the corneal transparency of mice in the hydrogel group was good, and no abnormal changes such as corneal edema, neovascularization, or inflammatory reactions were observed. The corneal fluorescein staining results of both groups of mice were negative, indicating that the integrity of the corneal epithelium was not damaged. Furthermore, the anterior chamber structure was clear, without obvious opacity or inflammation, indicating that the hydrogel did not cause significant ocular irritation or acute toxicity.

[0057] Optical coherence tomography (OCT) further revealed ( Figure 8 After two weeks of continuous administration, the corneal thickness of mice in the hydrogel group was not significantly different from that in the PBS control group. The corneal layer structure was clear and intact, and no abnormal thickening or structural disorder was observed.

[0058] The above results indicate that hydrogels, as ophthalmic drops, have good in vivo safety under short-term application conditions.

[0059] Example 9: Establishment of a Dry Eye Model Dilute 80% benzalkonium chloride solution to a concentration of 0.2% (w / v). Mice in the experimental group received 0.2% BAC intraconjunctival sac twice daily (8:00 and 20:00) for 14 consecutive days; the control group received PBS.

[0060] The therapeutic effect was systematically evaluated by detecting tear secretion and corneal damage in a dry eye model (DED) mouse. Compared with normal mice, the DED group mice showed a significant decrease in Schirmer's blood volume, accompanied by positive corneal fluorescein staining, indicating corneal epithelial defects and tear secretion dysfunction. Figure 9AC). After model establishment, there were no statistically significant differences in Schirmer's test and fluorescein staining scores among the experimental groups (P>0.05), indicating good consistency in model construction among the groups. Furthermore, during the 14-day period of 0.2% BAC induction, there were no significant differences in mouse body weight among the groups ( Figure 9 D), indicating that the modeling process did not cause significant systemic toxicity.

[0061] Example 10: Results of tear secretion detection and corneal fluorescein sodium staining After successful modeling, the mice were randomly divided into groups of 6: (1) PBS control group, (2) hydrogel group, (3) sDNA hydrogel group, and (4) DNT group. Each group was given 5 μL of the material or PBS eye drops. Each group was given 5 μL of different eye drops and manually blinked 5 times to promote uniform drug distribution. The treatment was administered twice daily for 14 consecutive days. Clinical evaluation was performed on days 0, 3, 5, 7, and 14 of the treatment.

[0062] After anesthetizing the mice, a phenol red cotton thread was placed at the outer 1 / 3 of the lower conjunctival fornix and held for 20 s. The length of the stained wetted area (mm) was measured to assess tear secretion function.

[0063] Mice were randomly divided into PBS group, hydrogel group, hydrogel + DNT group and DNT group. The mice were given eye drops twice daily and were followed up and evaluated on days 0, 3, 5, 7 and 14.

[0064] 2 μL of 2.5% sodium fluorescein solution was dropped into the conjunctival sac. After 1 min, the corneal fluorescence staining was observed and photographed under a slit-lamp microscope equipped with a cobalt blue filter to assess the degree of corneal epithelial damage.

[0065] With prolonged treatment, the length of phenol red cotton threads in mice in both the hydrogel group and the hydrogel + DNT group gradually increased, indicating a gradual recovery of tear secretion function. After 14 days of treatment, the cotton thread length in both groups was close to the normal control level and significantly higher than that in the PBS group and the DNT group. In contrast, tear secretion in the PBS group remained at a low level. These results indicate that hydrogel can significantly improve tear secretion function in dry eye model mice. Figure 10 B).

[0066] Corneal epithelium was stained with sodium fluorescein and observed and recorded under a slit-lamp microscope equipped with a cobalt blue filter. Compared with the PBS group, the hydrogel treatment group showed a faster trend of corneal epithelial healing at all time points. The area stained with fluorescein gradually decreased with prolonged treatment. After 14 days of treatment, significant corneal epithelial defects were still visible in the PBS group, while the corneal epithelium in the hydrogel group was basically restored to its original state, and fluorescein staining was negative or significantly weakened. Quantitative scoring of corneal healing rate revealed that the incidence of corneal ulceration was significantly lower in the hydrogel group compared to the PBS group. Figure 10 A).

[0067] The above results indicate that hydrogels can effectively promote corneal epithelial repair, reduce ocular surface damage, and thus improve the clinical performance of dry eye model mice.

[0068] Example 11: Histopathological Analysis of Ocular Tissue After treatment, mice were euthanized, and their eyeballs and surrounding tissues were harvested. These tissues were fixed in 4% paraformaldehyde for at least 24 hours, embedded in paraffin, and 5 μm sagittal sections were prepared. Hematoxylin-eosin (H&E) and PAS staining were performed. Images were acquired and observed using an optical microscope.

[0069] H&E staining results ( Figure 11 A) shows that the corneal epithelial structure in the normal group was intact, with clear layers, regular stroma arrangement, and a corneal epithelial thickness of 80.1 μm, without inflammatory cell infiltration. The corneal epithelium in the Model group was significantly thinner, with disordered local epithelial cell arrangement, a thickness of 72.5 μm, accompanied by varying degrees of structural discontinuity and inflammatory changes, indicating successful establishment of the dry eye model. The tissue structure in the DNT group was slightly improved compared to the Model group, but epithelial irregularities and mild tissue damage were still visible, with a corneal epithelial thickness of 78 μm. In contrast, the corneal epithelial layers in the Hydrogel group and the Hydrogel+DNT group were more completely restored, with corneal epithelial thicknesses of 80.1 μm and 78.6 μm respectively, showing significant improvement in epithelial thickness, a more regular stromal structure, and a significant reduction in inflammatory response. The degree of tissue structure recovery in the Hydrogel+DNT group was close to that of the normal group.

[0070] PAS staining results ( Figure 11 B) Primarily used to observe the condition of conjunctival goblet cells. Abundant PAS-positive goblet cells (purple-red staining) were observed in the conjunctival epithelium of the normal group. The number of goblet cells was significantly reduced in the Model group, indicating impaired tear film mucin secretion. The number of goblet cells in the DNT group was slightly increased compared to the Model group, but still below normal levels. The number of goblet cells was significantly increased in the Hydrogel group and the Hydrogel+DNT group, with a more regular arrangement and a clear recovery trend, among which the combined treatment group showed the most significant improvement.

[0071] The comprehensive histological results showed that the DNA hydrogel could effectively improve corneal epithelial structural damage in dry eye model mice and promote the recovery of conjunctival goblet cells, thus verifying its positive role in ocular surface repair and tear film function reconstruction from a histological perspective.

[0072] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A functionalized DNA hydrogel, characterized in that: The DNA hydrogel includes an EA module and an EB module; The EA module comprises six DNA strands, namely E1, E2, E3, E4, E5, and E6. The nucleotide sequence of the E1 DNA strand is shown in SEQ ID NO.1, the nucleotide sequence of the E2 DNA strand is shown in SEQ ID NO.2, the nucleotide sequence of the E3 DNA strand is shown in SEQ ID NO.3, the nucleotide sequence of the E4 DNA strand is shown in SEQ ID NO.4, the nucleotide sequence of the E5 DNA strand is shown in SEQ ID NO.5, and the nucleotide sequence of the E6 DNA strand is shown in SEQ ID NO.

6.

2. The functionalized DNA hydrogel according to claim 1, characterized in that: The EB module comprises two DNA strands, E7 and E8, with the nucleotide sequence of the E7 DNA strand shown in SEQ ID NO.7 and the nucleotide sequence of the E8 DNA strand shown in SEQ ID NO.

8.

3. The method for preparing the functionalized DNA hydrogel according to claim 1 or 2, characterized in that: Includes the following steps: (1) Mix E1 DNA chain, E2 DNA chain, E3 DNA chain, E4 DNA chain, E5 DNA chain and E6 DNA chain, add auxiliary assembly agent to it, and after mixing, obtain a reaction system. Perform thermal annealing on the reaction system to obtain EA module. (2) Mix the E7 DNA strand and the E8 DNA strand, add an assembly aid, and mix to obtain a reaction system. Perform thermal annealing on the reaction system to obtain the EB module. (3) Mix the EA module and the EB module evenly to obtain the final product.

4. The functionalized DNA hydrogel according to claim 3, characterized in that: The molar ratio of E1 DNA chain, E2 DNA chain, E3 DNA chain, E4 DNA chain, E5 DNA chain, E6 DNA chain, E7 DNA chain and E8 DNA chain in step (1) is 1:1:1:1:1:1:1:

1.

5. The functionalized DNA hydrogel according to claim 3, characterized in that: The auxiliary assembly agent in step (1) is magnesium sulfate, and the final concentration of magnesium ions in the reaction system in step (1) is about 7.5 mM; the working concentration of each DNA strand in the reaction system in step (1) is 800 μM. The auxiliary assembly agent in step (2) is magnesium sulfate, and the final concentration of magnesium ions in the reaction system in step (2) is about 7.5 mM; the working concentration of each DNA strand in the reaction system in step (2) is 800 μM.

6. The functionalized DNA hydrogel according to claim 3, characterized in that: The heat annealing process in step (1) is as follows: first, maintain the temperature at 95°C for 5 minutes, and then cool down from 93°C to 37°C at a gradient cooling rate of 1°C / min; the heat annealing process in step (2) is as follows: first, maintain the temperature at 95°C for 5 minutes, and then cool down from 93°C to 37°C at a gradient cooling rate of 1°C / min.

7. The use of the functionalized DNA hydrogel according to claim 1 or 2 in the preparation of ophthalmic medical devices.

8. The application of the functionalized DNA hydrogel according to claim 7 in the preparation of ophthalmic medical devices, characterized in that: The application of the functionalized DNA hydrogel in the preparation of orthodontic devices.

9. The application of the functionalized DNA hydrogel according to claim 8 in the preparation of ophthalmic medical devices, characterized in that: The application of the functionalized DNA hydrogel in the preparation of corneal contact lenses.

10. The application of the functionalized DNA hydrogel according to claim 9 in the preparation of ophthalmic medical devices, characterized in that: The application of the functionalized DNA hydrogel in the preparation of orthokeratology lenses.